Oodles of noodles - Hendry, Diana, 1941-; Massini, Sarah (Wilton, CT : Tiger Tales, 2008)
Ava and Ben's mom, Mrs. Mungo has a new pasta-making machine. But as soon as Ava and Ben go to school, the pasta maker begins working all by itself. Noodles fill the house, slither down the sidewalk and even show up at Ava and Ben's school. It's up to Ava and Ben to stop the flood of noodles.
Originally published: Great Britain : Little Tiger Press, 2007.
Keywords: Noodles; Noodles -- Juvenile fiction; Pasta machines -- Juvenile fiction